PEMBUATAN KARYA FOTOGRAFI PADA SAAT PPKM DARURAT COVID 19 DENGAN MENGGUNAKAN GAYA STREET PHOTOGRAPHY DI YOGYAKARTA - Hans Hermang Mintana (AKADEMI KOMUNIKASI RADYA BINATAMA, 2021)
With the increasing number of COVID-19 cases in Indonesia, the government was forced to adopt an Emergency PPKM policy throughout Java and Bali. This has great potential in capturing moments that occur in public spaces. These moments can be captured using Street Photography techniques. This technique is a technique that uses a candid approach in making his work so that it can bring out the honesty of the expressions of the subjects in this photo work. Yogyakarta itself was chosen because this city is the city that has the most impact on the implementation of the Emergency PPKM policy. The method of creation in this work is using exploration and improvisation techniques. The concept in the creation of this work is to capture the moments that occur in public spaces in Yogyakarta in the form of events that occurred during the implementation of the Java Bali Emergency PPKM policy. The process of making this work relies on the use of a Fujifilm XA-5 mirrorless camera with a kit lens from that series. The creation of this work resulted in 16 works with the title Jogja PPKM Emergency, Quiet, Taking Photo of Me, Through by, Romana, Empty, Close, Reflection, Quality time, Pursue me, Social Distancing by reduce social gathering, Bregodo, Dhedhe, Terlelap #1 , Sleeping #2 and No Day Off.